STRATEGY FOR INCREASING THE EFFICIENCY OF A MODERN INNOVATION SYSTEM IN THE PRODUCTION PROCESS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores strategies for enhancing the efficiency of modern innovation systems within production processes. It highlights the role of advanced technologies, such as artificial intelligence, the Internet of Things (IoT), and automation, in optimizing resource utilization, improving product quality, and reducing costs. The study outlines key approaches, including the integration of innovative systems, process optimization, and employee training. Additionally, the article examines the economic, social, and ecological impacts of implementing these systems. The research provides a comprehensive framework for organizations seeking to enhance competitiveness and sustainability in a rapidly evolving industrial landscape.